Human Trafficking (Prostitution) Interpretation of QS An-Nur 33 - Yusuf Agustian, Muhammad; Al Azimi, Zulfadli (Jurnal Multidisiplin Indonesia, 2023)
Trading humans (Human Trafficking) is increasingly crowded in various developing countries, including Indonesia. Women and children often become objects in trading humans because group women and children are considered as more people. Trading goals man Not only For prostitution or form exploitation sexual others but also includes form other exploits such as slavery, workforce, labour children, even selling body organs. Activity trading men like this often start from activity and later migration exploited by unscrupulous individuals, even a group of people who aren't moral and don't have enough mature thinking .